Evaluating Agricultural Extension and Advisory Services through a Governance Lens - Cristina Álvarez-Mingote; Paul E. McNamara (Journal of International Agricultural and Extension Education, 2018)
Demand-driven extension services have been promoted as a potential mechanism to improve governance quality and lead to better-served farmers. In this paper, we evaluate i) the extent to which demand-driven elements are present in extension services in developing countries, and ii) whether governance problems persist and why. We accomplish so by performing a qualitative analysis of the Modernizing Extension and Advisory Services (MEAS) country assessments, and find that, despite the adoption of demand-driven features, extension services are not fully participatory, transparent, accountable, equitable and responsive to needed farmers.
Keywords: extension and advisory services; demand-driven; good governanc